The Comptroller and Auditor General: reform the institution to enforce government's accountability - Mathur, B.P. (2018)
The Comptroller and Auditor General (CAG) is an institution under our con-stitution for enforcing the accountability of the executive and watching that public money is used with due regard to wisdom, faithfulness and economy. To perform the job efficiently, there is need for fundamental restructuring of its organisational structure, which is an inheritance from the colonial past. There is a need to convert it into a multi-member audit commission at the apex level and strengthen status of State Accountants General, who conduct the audit of state government transactions, by giving them statutory recognition and greater autonomy. To instil public confidence in the incumbent holding the high office of CAG, there is need for transparency in his appointment and only a professional of proven competence should be appointed to the post. Government should recognise the important role CAG can play in effective management of national finances and good governance. - Reproduced.
Keywords: Accountability; Audit; Public audit